Bimbingan Membaca Terhadap Abk Tuna Rungu - Cikal Jiwani Putri; Lilis Syahputri; Surahman (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2021)
The illiteracy rate in Indonesia reaches 1.71 percent or 2,961,060 people of the total population of Indonesia and the reading interest of Indonesian citizens is still very minimal, which is only 0.001 percent. Given that reading has a big role in human life and is the basis of learning, efforts to overcome it all need to be done. In this case the authors review from different objects, namely the deaf children with special needs or special guidance to learn to read because of their limitations in the senses of hearing and pronunciation. key and review of journal or book citations that are relevant to the article title. From a series of research methods, it was found that the method of reading guidance for deaf children can be done using the Maternal Reflective Method (MMR) and Synthetic Analysis Structure (SAS) which is added with visual media that supports learning in deaf children.